Antagonizing dabigatran by idarucizumab in cases of ischemic stroke or intracranial hemorrhage in Germany—Updated series of 120 cases. Issue 6 (August 2020) - Kermer, Pawel; Eschenfelder, Christoph C; Diener, Hans-Christoph; Grond, Martin; Abdalla, Yasser; Abraham, Alexej; Althaus, Katharina; Becks, Gebhard; Berrouschot, Jörg; Berthel, Jörg; Bode, Felix J.; Burghaus, Lothar; et al.
Background: Idarucizumab is a monoclonal antibody fragment with high affinity for dabigatran reversing its anticoagulant effects within minutes. Thereby, patients with acute ischemic stroke who are on dabigatran treatment may become eligible for thrombolysis with recombinant tissue-type plasminogen activator (rt-PA). In patients on dabigatran with intracerebral hemorrhage idarucizumab could prevent lesion growth. Aims: To provide insights into the clinical use of idarucizumab in patients under effective dabigatran anticoagulation presenting with signs of acute ischemic stroke or intracranial hemorrhage. Methods: Retrospective data collected from German neurological/neurosurgical departments administering idarucizumab following product launch from January 2016 to August 2018 were used. Results: One-hundred and twenty stroke patients received idarucizumab in 61 stroke centers. Eighty patients treated with dabigatran presented with ischemic stroke and 40 patients suffered intracranial bleeding (intracerebral hemorrhage (ICH) in n  = 27). In patients receiving intravenous thrombolysis with rt-PA following idarucizumab, 78% showed a median improvement of 7 points in National Institutes of Health Stroke Scale. No bleeding complications were reported. Hematoma growth was observed in 3 out of 27 patients with ICH. Outcome was favorable with a median National Institutes of Health Stroke Scale improvement of 4 points and modified Rankin score 0–3 in 61%. Six out of 40 individuals (15%) with intracranial bleeding died during hospital stay. Conclusion: Administration of rt-PA after reversal of dabigatran activity with idarucizumab in case of acute ischemic stroke seems feasible, effective, and safe. In dabigatran-associated intracranial hemorrhage, idarucizumab appears to prevent hematoma growth and to improve outcome.